Feline mammary carcinoma-derived extracellular vesicle promotes liver metastasis via sphingosine kinase-1-mediated premetastatic niche formation - Chang, Yi-Chih; Liu, Hao-Ping; Chuang, Hsiao-Li; Liao, Jiunn-Wang; Kao, Pei-Ling; Chan, Hsun-Lung; Chen, Ter-Hsin; Wang, Yu-Chih (Laboratory animal research, 2023)
Feline mammary carcinoma (FMC) is one of the most prevalent malignancies of female cats. FMC is highly metastatic and thus leads to poor disease outcomes. Among all metastases, liver metastasis occurs in about 25% of FMC patients. However, the mechanism underlying hepatic metastasis of FMC remains largely uncharacterized.BACKGROUNDFeline mammary carcinoma (FMC) is one of the most prevalent malignancies of female cats. FMC is highly metastatic and thus leads to poor disease outcomes. Among all metastases, liver metastasis occurs in about 25% of FMC patients. However, the mechanism underlying hepatic metastasis of FMC remains largely uncharacterized.Herein, we demonstrate that FMC-derived extracellular vesicles (FMC-EVs) promotes the liver metastasis of FMC by activating hepatic stellate cells (HSCs) to prime a hepatic premetastatic niche (PMN). Moreover, we provide evidence that sphingosine kinase 1 (SK1) delivered by FMC-EV was pivotal for the activation of HSC and the formation of hepatic PMN. Depletion of SK1 impaired cargo sorting in FMC-EV and the EV-potentiated HSC activation, and abolished hepatic colonization of FMC cells.RESULTSHerein, we demonstrate that FMC-derived extracellular vesicles (FMC-EVs) promotes the liver metastasis of FMC by activating hepatic stellate cells (HSCs) to prime a hepatic premetastatic niche (PMN). Moreover, we provide evidence that sphingosine kinase 1 (SK1) delivered by FMC-EV was pivotal for the activation of HSC and the formation of hepatic PMN. Depletion of SK1 impaired cargo sorting in FMC-EV and the EV-potentiated HSC activation, and abolished hepatic colonization of FMC cells.Taken together, our findings uncover a previously uncharacterized mechanism underlying liver-metastasis of FMC and provide new insights into prognosis and treatment of this feline malignancy.CONCLUSIONSTaken together, our findings uncover a previously uncharacterized mechanism underlying liver-metastasis of FMC and provide new insights into prognosis and treatment of this feline malignancy.